Dental care and personal protective measures for dentists and non-dental health care workers (2020)
COVID-19 infection not only poses significant risks to health care workers, but to dentists and dental health care workers, owing to the potential prolonged exposure and proximity to patients. This holds true for non-dentist health care workers who often in the setting of emergency departments and urgent care centers are tasked with addressing oral symptoms including abscesses, damaged teeth, jaw injuries and other dental urgencies. Infection control practice guidelines were evaluated for COVID-19 infection prevention in a dental setting. In this brief review, protective measures to reduce the risk of COVID-19 infection for dentists and non-dentist health care providers will be introduced. This includes patient evaluation, personal and patient protective equipment use, sterilization and disinfection protocols.